Attributing salmonellosis cases to foodborne, animal contact and waterborne routes using the microbial subtyping approach and exposure weights. (June 2023) - Hurst, Matt; Nesbitt, Andrea; Kadykalo, Stefanie; Dougherty, Brendan; Arango-Sabogal, Juan Carlos; Ravel, André
Abstract: Salmonella is a major cause of enteric disease in Canada. Cases of salmonellosis were attributed to retail meats, food animal manure contact, and surface water sources using a microbial subtyping approach coupled with adjustments for exposure. Results indicated that 64.7% of cases were attributed to chicken breast meat, followed by frozen raw breaded chicken products (12.9%), ground chicken (9.1%), water (3.0%), pork chops and sausage (1.3%), ground beef and veal (0.7%), turkey parts (0.5%), and molluscs (0.0%). The salmonellosis incidence rate in the FoodNet Canada sentinel sites fell by one third with a parallel drop of one third in the percent of cases attributed to chicken breast meat between 2015 and 2019. Decreases in the contribution of many of the top serovars to the percentage of cases attributed to chicken breast meat indicates some emerging success with broiler breeder chicken vaccination programs. In addition, preliminary prevalence results for frozen raw chicken products in late 2019 suggests the Canadian Food Inspection Agency intervention in 2019 requiring any Salmonella on these products to be below a detectable amount may be having an impact, though more data post intervention is needed to be more conclusive. Highlights: Salmonellosis cases were attributed to foodborne, animal contact, water sources yearly to detect the impact of interventions. Chicken meat was the most important source, with some yearly variations between specific chicken products. Industry and government interventions having a positive impact in reducing salmonellosis cases and chicken-related serovars.